Skáldleg afbrotafræði skáldsaga - Einar Már Guðmundsson 1954- (Mál og menning, 2021)
This novel gives a picture of an Icelandic society in a small village sometime in the eighteenth century. All kinds of stories criss-cross and weave from one person and point to another. Well knitted by master craftsman Einar Már Guðmundsson. Sheds a light on Icelandic history and sadness and oppression, freedom and hope.